Preparation method of irradiation-resistant and accident-resistant SiC / SiC nuclear fuel cladding
By designing alternating PyC and SiC nanowire multi-layer interface structures in SiC/SiC composites, the problem of volume changes in SiC/SiC composites in the irradiated environment in the nuclear energy system is solved, and the SiC/SiC nuclear fuel cladding is realized. Improved radiation resistance and optimized mechanical properties.
Patent Information
- Application Number
- CN202310830292.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
AI Technical Summary
When SiC/SiC composites are irradiated by neutrons in nuclear energy systems, the thermal neutron absorption and irradiation swelling of the interface phase lead to a degradation of performance. The existing PyC interface changes in volume under neutron radiation, and the cost of the MAX phase interface is high. And it is not yet mature, and it is difficult to maintain volume stability under an irradiated environment.
Design a multi-layer interface with alternating structures, including at least two PyC interface layers and at least one SiC nanowire interface layer, and deposition and densification on the surface of the SiC fiber prefabricated body through a chemical vapor deposition process to form a SiC/SiC nuclear fuel cladding. to alleviate irradiation stress and volume effects.
The volume stability and excellent mechanical properties of SiC/SiC nuclear fuel cladding in high dose irradiation environment are achieved. The SiC nanowires are uniformly distributed, the morphology and volume fraction are controllable, and the process is simple and versatile.
Smart Images

Figure CN119263859A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of SiC materials, and in particular relates to a method for preparing a radiation-resistant and accident-resistant SiC / SiC nuclear fuel cladding. Background Art
[0003] SiC / SiC composites have excellent properties such as high strength, non-brittle fracture, high thermal conductivity, hydrothermal corrosion resistance, and low thermal neutron absorption cross section, and are important candidate materials for accident-resistant nuclear fuel cladding. The interface phase is an indispensable part of ceramic matrix composites, which can play the role of "mechanical fuse" and "load transfer". When SiC / SiC composites are used in nuclear energy systems, the materials are inevitably irradiated by neutrons. The third-generation SiC fiber braided preform and the SiC matrix obtained by chemical vapor infiltration (CVI) have good radiation resistance. At this time, the interface, as a crucial factor affecting the performance of ceramic matrix composites, often becomes the weak link of SiC / SiC composites.
[0004] BN or PyC is usually used as the interface phase in the preparation of ceramic-based composite materials. However, the thermal neutron absorption cross section of the BN interface is high, and the helium generated by the thermal neutron reaction of B (n, α) will increase the radiation swelling of the composite material, significantly reducing the mechanical and thermal properties of the material, and is not suitable for use in nuclear energy systems. PyC is the most widely used interface phase of ceramic-based composite materials, and its engineering development is the most mature. Chinese patents (publication number CN103818056A) and (publication number CN112374902A) disclose methods for preparing SiC / SiC accident-resistant nuclear fuel cladding with PyC as the interface phase. However, PyC has spatial anisotropy characteristics, and it will undergo directional property changes under neutron irradiation, and the accompanying volume change effect will also have an adverse effect on the performance of nuclear composite materials. The MAX phase interface has a special layered structure and excellent radiation resistance. In addition, the recent literature "LiM, Wang K, Wang J, et al. Preparation of TiC / Ti2AlC coating on carbon fiber and investigation of the oxidation resistance properties [J]. Journal of the American Ceramic Society, 2018, 101 (11): 5269-5280" reported a new MAX phase interface, which has great potential as an interface phase for nuclear ceramic matrix composites, but the MAX phase interface is still in the laboratory research stage and the cost is extremely high. Taking the above factors into consideration, optimizing the existing PyC interface so that the interface phase maintains a certain volume stability under irradiation environment is the most economical and effective means to improve the radiation resistance of SiC / SiC accident-resistant nuclear fuel cladding. Summary of the invention
[0005] The present invention aims to overcome the defect of insufficient radiation resistance of existing SiC / SiC composite materials, and provides a method for preparing radiation-resistant and accident-resistant SiC / SiC nuclear fuel cladding by designing an alternating structure of at least two PyC interface layers and at least one SiC nanowire (SiCnw) interface layer to alleviate the radiation stress and volume effect.
[0006] The present invention provides a method for preparing a radiation-resistant and accident-resistant SiC / SiC nuclear fuel cladding, comprising: (1) alternately performing the following steps (A) and (B) in a manner starting from step (A) and ending with step (A) to obtain a tubular SiC fiber preform having at least two PyC interface layers and at least one SiC nanowire interface layer: (A) depositing a PyC interface layer on the surface of a tubular SiC fiber preform by a chemical vapor deposition process, wherein the thickness of the PyC interface layer is 100 to 200 nm; (B) immersing the tubular SiC fiber preform with a PyC interface layer deposited thereon obtained in step (A) into a catalyst solution, loading the catalyst onto the PyC interface layer by vacuum impregnation, and then in-situ generating a SiC nanowire interface layer on the surface of the PyC interface layer by a chemical vapor deposition process; the catalyst solution comprises a metal ion catalyst precursor, a surface modifier and a solvent, wherein the volume ratio of the metal ion catalyst precursor, the surface modifier and the solvent is (10-20):1:(200-500); the diameter of the SiC nanowires in the SiC nanowire interface layer is 100-300 nm, the aspect ratio is (20-5):1, and the thickness of the SiC nanowire interface layer is 400-800 nm; (2) densifying a tubular SiC fiber preform having at least two PyC interface layers and at least one SiC nanowire interface layer by a chemical vapor infiltration process; (3) A SiC coating is deposited on the surface of a tubular SiC fiber preform having at least two PyC interface layers and at least one SiC nanowire interface layer by a chemical vapor deposition process to obtain the SiC / SiC nuclear fuel cladding tube.
[0007] Preferably, the tubular SiC fiber preform is a hollow SiC fiber tube formed by winding and braiding third-generation SiC fibers.
[0008] Preferably, in step (A), the parameters of the chemical vapor deposition process are: using liquefied petroleum gas as the source material, using argon as the diluent gas, and the total gas flow rate is 0.5 to 1.5 m 3 / h, the flow ratio of liquefied petroleum gas and argon is 1:(1~3), the deposition temperature is 800~1100℃, and the deposition time is 70~140h.
[0009] Preferably, in step (B), the metal ion catalyst precursor is a nitrate of a transition metal; the transition metal is iron, chromium or nickel; the surface modifier is at least one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide and polyethylene glycol; and the solvent is at least one of ethanol, methanol and acetone.
[0010] Preferably, in step (B), the parameters of the vacuum impregnation are: vacuum degree of 5 to 10 kPa, and impregnation time of 0.5 to 1.5 h.
[0011] Preferably, in step (B), the parameters of the chemical vapor deposition process are: evacuating to 300-3000 Pa, introducing dilution gas Ar at a flow rate of 400-800 mL / min, introducing carrier gas Ar / H2 at a flow rate of 40-400 mL / min into the silane gas preheated to a temperature higher than its boiling point, heating to 1000-1300°C at a rate of 5-10°C / min, keeping warm for 20-50 hours, and then cooling to room temperature at a rate of 5-10°C / min; wherein the flow ratio of Ar / H2 in the carrier gas is 1:(1-3), the silane gas is trichloromethylsilane, and the flow ratio of the carrier gas to trichloromethylsilane is (8-12):1.
[0012] Preferably, in step (2), the parameters of the chemical vapor infiltration process include: evacuating to 100-1000 Pa, introducing dilution gas Ar at a flow rate of 400-800 mL / min, and introducing carrier gas Ar / H2 at a flow rate of 40-400 mL / min into silane gas that has been preheated to a temperature higher than its boiling point; wherein the deposition temperature is 800-1000°C, and the deposition time is 140-240 h; the flow ratio of Ar / H2 in the carrier gas is 1:(1-3), the silane gas is trichloromethylsilane, and the flow ratio of the carrier gas to trichloromethylsilane is (8-12):1.
[0013] Preferably, in step (3), the parameters of the chemical vapor deposition process include: evacuating to 300-3000 Pa, introducing dilution gas Ar at a flow rate of 400-800 mL / min, and introducing carrier gas Ar / H2 at a flow rate of 40-400 mL / min into silane gas that has been preheated to a temperature higher than its boiling point; wherein the deposition temperature is 1000-1300°C, and the deposition time is 70-120 h; the flow ratio of Ar / H2 in the carrier gas is 1:(1-3), the silane gas is trichloromethylsilane, and the flow ratio of the carrier gas to trichloromethylsilane is (8-12):1.
[0014] In the present invention, by controlling the types of metal ion catalyst precursors and surface modifiers and their ratio with the solvent, combined with a precisely controlled CVD process, various parameters of the SiCnw interface layer, including thickness, nanowire morphology and aspect ratio, are precisely controlled, thereby making the volume stability of the multilayer interface better in a high-dose irradiation environment, and finally obtaining a radiation-resistant and accident-resistant SiC / SiC nuclear fuel cladding.
[0015] Beneficial effects:
[0016] The radiation-resistant and accident-resistant SiC / SiC nuclear fuel cladding of the present invention has the following advantages:
[0017] (1) SiCnw is evenly distributed between the PyC interface layers and basically does not agglomerate itself.
[0018] (2) The morphology and volume fraction of SiCnw are controllable, the process is simple and has certain versatility.
[0019] (3) The SiCnw interface layer and the PyC interface layer in the interface phase form a multi-level reinforcement mode, which gives the cladding tube excellent mechanical properties.
[0020] (4) The alternating interface layers of PyC and SiCnw make the nuclear fuel cladding exhibit excellent volume stability under high-dose irradiation environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a process flow chart of the present invention; Figure 2 This is an X-ray CT scan image of the radiation-resistant and accident-resistant SiC / SiC nuclear fuel cladding tube in Example 1; Figure 3 Schematic diagram of the microstructure of the SiC / SiC nuclear fuel cladding tube with the five-layer structure interface phase (PyC / SiCnw / PyC / SiCnw / PyC) in Example 2; Figure 4 (a) SiC / SiC composite material with a multilayer interface phase structure; (b) multilayer interface phase microstructure; (c) SiC interface phase microstructure in the multilayer interface phase. DETAILED DESCRIPTION
[0022] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.
[0023] The following is an exemplary description of the method for preparing the radiation-resistant and accident-resistant SiC / SiC nuclear fuel cladding provided by the present invention (eg Figure 1 shown).
[0024] The following steps (A) and (B) are alternately performed in a manner starting from step (A) and ending at step (A) to obtain a tubular SiC fiber preform having at least two PyC interface layers and at least one SiC nanowire (SiCnw) interface layer.
[0025] The tubular SiC fiber preform may be a hollow SiC fiber tube formed by winding and braiding third generation SiC fibers.
[0026] (A) A PyC interface layer is deposited on the surface of a tubular SiC fiber preform by a chemical vapor deposition process, wherein the thickness of the PyC interface layer is 100 to 200 nm.
[0027] (B) The tubular SiC fiber preform deposited with the PyC interface layer obtained in step (A) is immersed in a catalyst solution, the catalyst is loaded onto the PyC interface layer by vacuum impregnation, and then a SiC nanowire interface layer is generated in situ on the surface of the PyC interface layer by a chemical vapor deposition process. The catalyst solution comprises a metal ion catalyst precursor, a surface modifier and a solvent, and the volume ratio of the metal ion catalyst precursor, the surface modifier and the solvent is (10-20):1:(200-500). If the volume ratio of the three is not within this range, it will not only affect the impregnation effect of the catalyst solution, but also have an adverse effect on the morphology control of the subsequent SiCnw interface layer. The diameter of the SiC nanowires in the SiC nanowire interface layer is 100-300nm, the aspect ratio is (20-5):1, and the thickness of the SiC nanowire interface layer is 400-800nm.
[0028] In an optional embodiment, in step (A), the parameters of the chemical vapor deposition process are: using liquefied petroleum gas as the source material, using argon as the diluent gas, and a total gas flow rate of 0.5 to 1.5 m 3 / h, the flow ratio of liquefied petroleum gas and argon is 1:(1~3), the deposition temperature is 800~1100℃, and the deposition time is 70~140h.
[0029] In step (B), the metal ion catalyst precursor is a nitrate of a transition metal; the transition metal is iron, chromium or nickel; the conversion product of the metal ion catalyst precursor at high temperature will become a preferential nucleation site for SiCnw, promoting the stacking of the SiC gaseous precursor along the preferential growth direction of SiC whiskers; the surface modifier is at least one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and polyethylene glycol; the solvent is at least one of ethanol, methanol, and acetone.
[0030] In step (B), the parameters of the vacuum impregnation are: vacuum degree of 5-10 kPa, and impregnation time of 0.5-1.5 h. The present invention can fully infiltrate the catalyst solution into the porous fiber preform through vacuum impregnation, thereby promoting the subsequent in-situ generation reaction of SiCnw from the perspective of reaction kinetics.
[0031] In step (B), the parameters of the chemical vapor deposition process are: evacuating to 300-3000 Pa, introducing dilution gas Ar at a flow rate of 400-800 mL / min, introducing carrier gas Ar / H2 at a flow rate of 40-400 mL / min into silane gas that has been preheated to a temperature higher than its boiling point (for example, the silane gas is heated to a temperature higher than its boiling point by water bath heating), heating to 1000-1300°C at a rate of 5-10°C / min, keeping warm for 20-50 hours, and then cooling to room temperature at a rate of 5-10°C / min; wherein the flow ratio of Ar / H2 in the carrier gas is 1:(1-3), the silane gas is trichloromethylsilane, and the flow ratio of the carrier gas to trichloromethylsilane is (8-12):1.
[0032] A chemical vapor infiltration process is used to densify a tubular SiC fiber preform having at least two PyC interface layers and at least one SiC nanowire interface layer.
[0033] In an optional embodiment, the parameters of the chemical vapor infiltration process include: evacuating to 100-1000 Pa, introducing dilution gas Ar at a flow rate of 400-800 mL / min, and introducing carrier gas Ar / H2 at a flow rate of 40-400 mL / min into silane gas that has been preheated to a temperature higher than its boiling point; wherein the deposition temperature is 800-1000°C, and the deposition time is 140-240 h; the flow ratio of Ar / H2 in the carrier gas is 1:(1-3), the silane gas is trichloromethylsilane, and the flow ratio of the carrier gas to trichloromethylsilane is (8-12):1.
[0034] The SiC / SiC nuclear fuel cladding tube is obtained by depositing a SiC coating on the surface of a tubular SiC fiber preform having at least two PyC interface layers and at least one SiC nanowire interface layer using a chemical vapor deposition process.
[0035] In an optional embodiment, the parameters of the chemical vapor deposition process include: evacuating to 300-3000 Pa, introducing dilution gas Ar at a flow rate of 400-800 mL / min, and introducing carrier gas Ar / H2 at a flow rate of 40-400 mL / min into silane gas that has been preheated to a temperature higher than its boiling point; wherein the deposition temperature is 1000-1300°C, and the deposition time is 70-120 h; the flow ratio of Ar / H2 in the carrier gas is 1:(1-3), the silane gas is trichloromethylsilane, and the flow ratio of the carrier gas to trichloromethylsilane is (8-12):1.
[0036] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0037] Example 1
[0038] (1) After the third-generation SiC fiber tube was ultrasonically cleaned and dried with acetone, it was deposited based on the CVD process with liquefied petroleum gas (mainly methane CH4) as the source material and argon as the dilution gas at a deposition temperature of 800 °C and a total gas flow rate of 1.5 m 3 / h (the flow ratio of methane to argon is 1:1), the reaction time is 100h, and the deposition of PyC interface layer on the surface of SiC fiber is completed.
[0039] (2) Using ferric nitrate as a catalyst precursor, PEG as a surface modifier, and acetone as a solvent, a metal ion catalyst solution is prepared at a volume ratio of 15:1:300; immersing the preform obtained in step (1) in the solution, maintaining it at a pressure of 8 kPa for 1 hour, and obtaining a fiber preform loaded with a catalyst.
[0040] (3) The catalyst-loaded fiber preform is placed in a chemical vapor reactor, first evacuated to 3000Pa, and diluted gas Ar is introduced at a flow rate of 600mL / min; carrier gas Ar / H2 (Ar / H2 volume ratio is 1:1) is introduced into trichloromethylsilane gas heated in a water bath to above the boiling point at a flow rate of 400mL / min, the flow ratio of carrier gas to trichloromethylsilane is 8:1, and the temperature is increased to 1200℃ at a heating rate of 8℃ / min, kept warm for 50h, and then cooled at a rate of 8℃ / min to obtain a fiber preform with a SiCnw composite interface layer grown on the PyC surface, and then the CVD process of step (1) is repeated once to obtain a fiber preform with a three-layer interface structure (PyC / SiCnw / PyC).
[0041] (4) The fiber preform of the interface phase obtained in step (3) is placed in a chemical vapor reactor, first evacuated to 500 Pa, and the dilution gas Ar is introduced at a flow rate of 400 mL / min; the carrier gas (Ar / H2 volume ratio is 1:2) is introduced into the trichloromethylsilane gas heated to above the boiling point in a water bath at a flow rate of 200 mL / min, the flow ratio of the carrier gas to the trichloromethylsilane is 8:1, the deposition temperature is 1000°C, the deposition time is 200 h, and the fiber preform is densified by SiC matrix to obtain a SiC / SiC cladding tube.
[0042] (5) The densified SiC / SiC cladding tube is placed in a chemical vapor reactor, first evacuated to 300 Pa, and the dilution gas Ar is introduced at a flow rate of 400 mL / min; the carrier gas (Ar / H2 volume ratio is 1:2) is introduced into the trichloromethylsilane gas heated to above the boiling point in a water bath at a flow rate of 40 mL / min, the flow ratio of the carrier gas to trichloromethylsilane is 10:1, the deposition temperature is 1000°C, and the deposition time is 100 h. SiC coating is prepared on the surface of the SiC / SiC cladding tube.
[0043] After testing, the thickness of the single-layer PyC interface and SiCnw interface are 110nm and 590nm respectively, and the distribution of the interface layer from the inside to the outside is PyC / SiCnw / PyC, with a total thickness of 0.77μm. The accident-resistant SiC / SiC nuclear fuel cladding was irradiated using an Am-Be neutron test source, and the diameter change rate of the cladding before and after irradiation was +0.3%. In addition, the axial tensile strength, hoop tensile strength and hoop compressive strength of the cladding before and after irradiation were tested according to ASTM C1773, ASTMC1819 and ASTM C1323, respectively, and the change rates were 4.7%, 11.2% and 6.2%, respectively, indicating that the accident-resistant SiC / SiC nuclear fuel cladding prepared by this method has excellent radiation resistance.
[0044] Figure 2 This is an X-ray CT scan image of the SiC / SiC nuclear fuel cladding tube in Example 1. It can be seen from the figure that its structure is dense, there are no obvious large pores, and a typical fiber weaving structure can be observed.
[0045] Example 2
[0046] (1) After the third-generation SiC fiber tube was ultrasonically cleaned and dried with acetone, it was deposited based on the CVD process with liquefied petroleum gas (mainly methane CH4) as the source material and argon as the dilution gas at a deposition temperature of 1000 °C and a total gas flow rate of 0.5 m 3 / h (the flow ratio of methane to argon is 1:3), and the reaction time is 140h to complete the deposition of the PyC interface layer on the SiC fiber surface.
[0047] (2) Using nickel nitrate as a catalyst precursor, SDS as a surface modifier, and methanol as a solvent, a metal ion catalyst solution is prepared at a volume ratio of 20:1:500; immersing the preform obtained in step (1) in the solution and maintaining it at a pressure of 5 kPa for 1.5 hours to obtain a fiber preform loaded with a catalyst.
[0048] (3) The catalyst-loaded fiber preform is placed in a chemical vapor reactor, first evacuated to 1500Pa, and diluted gas Ar is introduced at a flow rate of 800mL / min; the carrier gas (Ar / H2 volume ratio is 1:2) is introduced into a water bath heated to a trichloromethylsilane gas above the boiling point at a flow rate of 40mL / min, the flow ratio of the carrier gas to trichloromethylsilane is 10:1, the temperature is increased to 1000℃ at a heating rate of 10℃ / min and kept warm for 20h, and then cooled at a rate of 10℃ / min to obtain a fiber preform with a SiCnw composite interface layer grown on the PyC surface, and then the CVD process of step (1) is repeated once, the catalytic process of step (2) is repeated once, the CVD process of step (3) is repeated once, and the CVD process of step (1) is repeated once to obtain a fiber preform with a five-layer interface structure (PyC / SiCnw / PyC / SiCnw / PyC).
[0049] (4) The fiber preform with the prepared interface phase is placed in a chemical vapor reactor, first evacuated to 1000Pa, and the dilution gas Ar is introduced at a flow rate of 600mL / min; the carrier gas (Ar / H2 volume ratio is 1:1) is introduced into the trichloromethylsilane gas heated to above the boiling point in a water bath at a flow rate of 40mL / min, the flow ratio of the carrier gas to trichloromethylsilane is 10:1, the deposition temperature is 900℃, and the deposition time is 240h. The fiber preform is densified by SiC matrix to obtain a SiC / SiC cladding tube.
[0050] (5) The densified SiC / SiC cladding tube was placed in a chemical vapor reactor, first evacuated to 3000Pa, and the dilution gas Ar was introduced at a flow rate of 600mL / min; the carrier gas (Ar / H2 volume ratio of 1:3) was introduced into the trichloromethylsilane gas heated to above the boiling point in a water bath at a flow rate of 400mL / min, the flow ratio of the carrier gas to trichloromethylsilane was 12:1, the deposition temperature was 1150℃, and the deposition time was 120h, and the SiC coating was prepared on the surface of the SiC / SiC cladding tube.
[0051] After testing, the thickness of the single-layer PyC interface and SiCnw interface are 190nm and 640nm respectively, and the distribution of the interface layer from the inside to the outside is PyC / SiCnw / PyC / SiCnw / PyC, with a total thickness of 1.56μm. The accident-resistant SiC / SiC nuclear fuel cladding was irradiated using an Am-Be neutron test source, and the diameter change rate of the cladding before and after irradiation was +0.2%. In addition, the axial tensile strength, hoop tensile strength and hoop compressive strength of the cladding before and after irradiation were tested according to ASTMC1773, ASTM C1819 and ASTM C1323, respectively, and the change rates were -6.2%, -10.1% and -9.3%, respectively, indicating that the accident-resistant SiC / SiC nuclear fuel cladding prepared by this method has excellent radiation resistance.
[0052] Figure 3 This is a schematic diagram of the microstructure of the SiC / SiC nuclear fuel cladding tube with a five-layer structural interface phase (PyC / SiCnw / PyC / SiCnw / PyC) in Example 2, in which the SiCnw in the PyC interface phase can preferentially slow down the material structure changes under the action of force, heat, radiation, etc. due to its own network structure, thereby improving its structural stability.
[0053] Figure 4 (a) is a SiC / SiC composite material with a multilayer interface phase structure; (b) multilayer interface phase microstructure; (c) SiC interface phase microstructure in the multilayer interface phase. As can be seen from the figure, at low magnification, it can be observed that there is a multilayer structure on the outside of the fiber with a circular cross section. At medium magnification combined with EDS, it can be seen that its chemical composition is C, SiC, C, SiC and C. At high magnification, the interlocking network structure in the SiCnw interface phase can be observed, which is consistent with the Figure 3 The shown are basically consistent.
[0054] Example 3
[0055] (1) After the third-generation SiC fiber tube was ultrasonically cleaned and dried with acetone, it was deposited based on the CVD process with liquefied petroleum gas (mainly methane CH4) as the source material and argon as the dilution gas at a deposition temperature of 800 °C and a total gas flow rate of 1.5 m 3 / h (the flow ratio of methane to argon is 1:2), and the reaction is carried out for 100h to complete the deposition of the PyC interface layer on the SiC fiber surface.
[0056] (2) Using chromium nitrate as a catalyst precursor, CTAB as a surface modifier, and ethanol as a solvent, a metal ion catalyst solution is prepared at a volume ratio of 10:1:200; immersing the preform obtained in step (1) in the solution, maintaining it at a pressure of 10 kPa for 0.5 h, and obtaining a fiber preform loaded with a catalyst.
[0057] (3) The catalyst-loaded fiber preform is placed in a chemical vapor reactor, first evacuated to 300 Pa, and diluted gas Ar is introduced at a flow rate of 400 mL / min; the carrier gas (Ar / H2 volume ratio is 1:3) is introduced into a water bath heated to a trichloromethylsilane gas above the boiling point at a flow rate of 300 mL / min, the flow ratio of the carrier gas to trichloromethylsilane is 12:1, the temperature is increased to 1300°C at a heating rate of 5°C / min and kept warm for 40 hours, and then cooled at a rate of 5°C / min to obtain a fiber preform with a SiCnw composite interface layer grown on the PyC surface, and then the CVD process of step (1), the catalytic process of step (2) and the CVD process of step (3) are repeated in sequence to obtain a fiber preform with a 7-layer interface structure (PyC / SiCnw / PyC / SiCnw / PyC / SiCnw / PyC).
[0058] (4) The fiber preform with the prepared interface phase is placed in a chemical vapor reactor, first evacuated to 100 Pa, and the dilution gas Ar is introduced at a flow rate of 800 mL / min; the carrier gas (Ar / H2 volume ratio is 1:3) is introduced into the trichloromethylsilane gas heated to above the boiling point in a water bath at a flow rate of 400 mL / min, the flow ratio of the carrier gas to trichloromethylsilane is 12:1, the deposition temperature is 800°C, and the deposition time is 140 h. The SiC matrix of the fiber preform is densified to obtain a SiC / SiC cladding tube.
[0059] (5) The densified SiC / SiC cladding tube was placed in a chemical vapor reactor, first evacuated to 1000Pa, and the dilution gas Ar was introduced at a flow rate of 800mL / min; the carrier gas (Ar / H2 volume ratio of 1:1) was introduced into the trichloromethylsilane gas heated in a water bath to above the boiling point at a flow rate of 200mL / min, the flow ratio of carrier gas to trichloromethylsilane was 8:1, the reaction temperature was 1300℃, and the deposition time was 70h, and the SiC coating was prepared on the surface of the SiC / SiC cladding tube.
[0060] After testing, the thickness of the single-layer PyC interface and SiCnw interface are 200nm and 490nm respectively, and the distribution of the interface layer from inside to outside is PyC / SiCnw / PyC / SiCnw / PyC / SiCnw / PyC, with a total thickness of 1.95μm. The accident-resistant SiC / SiC nuclear fuel cladding was irradiated using an Am-Be neutron test source, and the diameter change rate of the cladding before and after irradiation was +0.1%. In addition, the axial tensile strength, hoop tensile strength and hoop compressive strength of the cladding before and after irradiation were tested according to ASTM C1773, ASTM C1819 and ASTM C1323, and the change rates were 7.2%, 13.7% and 10.7% respectively, indicating that the accident-resistant SiC / SiC nuclear fuel cladding prepared by this method has excellent radiation resistance.
Claims
1. A method for preparing a radiation-resistant and accident-resistant SiC / SiC nuclear fuel cladding, characterized in that: include: (1) alternately performing the following steps (A) and (B) in a manner starting from step (A) and ending with step (A) to obtain a tubular SiC fiber preform having at least two PyC interface layers and at least one SiC nanowire interface layer: (A) depositing a PyC interface layer on the surface of a tubular SiC fiber preform by a chemical vapor deposition process, wherein the thickness of the PyC interface layer is 100 to 200 nm; (B) immersing the tubular SiC fiber preform with a PyC interface layer deposited thereon obtained in step (A) into a catalyst solution, loading the catalyst onto the PyC interface layer by vacuum impregnation, and then in-situ generating a SiC nanowire interface layer on the surface of the PyC interface layer by a chemical vapor deposition process; the catalyst solution comprises a metal ion catalyst precursor, a surface modifier and a solvent, wherein the volume ratio of the metal ion catalyst precursor, the surface modifier and the solvent is (10-20):1:(200-500); the diameter of the SiC nanowires in the SiC nanowire interface layer is 100-300 nm, the aspect ratio is (20-5):1, and the thickness of the SiC nanowire interface layer is 400-800 nm; (2) densifying a tubular SiC fiber preform having at least two PyC interface layers and at least one SiC nanowire interface layer by a chemical vapor infiltration process; (3) A SiC coating is deposited on the surface of a tubular SiC fiber preform having at least two PyC interface layers and at least one SiC nanowire interface layer by a chemical vapor deposition process to obtain the SiC / SiC nuclear fuel cladding tube.
2. The preparation method according to claim 1, characterized in that: The tubular SiC fiber preform is a hollow SiC fiber tube formed by winding and weaving third-generation SiC fibers.
3. The preparation method according to claim 1 or 2, characterized in that: In step (A), the parameters of the chemical vapor deposition process are: liquefied petroleum gas as the source material, argon as the diluent gas, and a total gas flow rate of 0.5 to 1.5 m 3 / h, the flow ratio of liquefied petroleum gas and argon is 1:(1~3), the deposition temperature is 800~1100℃, and the deposition time is 70~140h.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step (B), the metal ion catalyst precursor is a nitrate of a transition metal; the transition metal is iron, chromium or nickel; the surface modifier is at least one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide and polyethylene glycol; and the solvent is at least one of ethanol, methanol and acetone.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (B), the parameters of the vacuum impregnation are: vacuum degree is 5-10 kPa, and the impregnation time is 0.5-1.5 h.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (B), the parameters of the chemical vapor deposition process are: evacuating to 300-3000 Pa, introducing dilution gas Ar at a flow rate of 400-800 mL / min, introducing carrier gas Ar / H2 at a flow rate of 40-400 mL / min into the silane gas preheated to a temperature higher than its boiling point, heating to 1000-1300°C at a rate of 5-10°C / min, keeping warm for 20-50 hours, and then cooling to room temperature at a rate of 5-10°C / min; wherein the flow ratio of Ar / H2 in the carrier gas is 1:(1-3), the silane gas is trichloromethylsilane, and the flow ratio of the carrier gas to trichloromethylsilane is (8-12):
1.
7. The preparation method according to any one of claims 1 to 6, characterized in that In step (2), the parameters of the chemical vapor infiltration process include: evacuating to 100-1000 Pa, introducing dilution gas Ar at a flow rate of 400-800 mL / min, and introducing carrier gas Ar / H2 at a flow rate of 40-400 mL / min into silane gas that has been preheated to a temperature higher than its boiling point; wherein the deposition temperature is 800-1000°C, and the deposition time is 140-240 hours; the flow ratio of Ar / H2 in the carrier gas is 1:(1-3), the silane gas is trichloromethylsilane, and the flow ratio of the carrier gas to trichloromethylsilane is (8-12):
1.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (3), the parameters of the chemical vapor deposition process include: evacuating to 300-3000 Pa, introducing dilution gas Ar at a flow rate of 400-800 mL / min, and introducing carrier gas Ar / H2 at a flow rate of 40-400 mL / min into silane gas that has been preheated to a temperature higher than its boiling point; wherein the deposition temperature is 1000-1300°C, and the deposition time is 70-120 h; the flow ratio of Ar / H2 in the carrier gas is 1:(1-3), the silane gas is trichloromethylsilane, and the flow ratio of the carrier gas to trichloromethylsilane is (8-12):1.
Citation Information
Patent Citations
Multilayer structure of SiC / SiC (silicon carbide) composite cladding tube and preparation method thereof
CN103818056A
Preparation method of high-compactness SiCf / SiC cladding composite pipe
CN112374902A
Method for preparing ceramic matrix composite material through SiC nano-wire modified ceramic matrix composite material interface
CN105237021A
Interface layer structure of SiCf / SiC composite material fuel cladding and preparation method
CN113004051A
SiC nanowire toughened PyC / SiC composite interface of SiCf / SiC composite material and preparation method of SiC nanowire toughened PyC / SiC composite interface
CN114315395A
Cited By
High-safety modular composite fuel element and preparation method thereof
CN121687592A
A high safety modular composite fuel element and a method for manufacturing the same
CN121687592B
Silicon carbide fiber reinforced silicon carbide composite material with in-situ growth nanowire interface layer as well as preparation method and application of silicon carbide fiber reinforced silicon carbide composite material
CN122233804A